Adding the missing voice: How self-report of autistic youth self-report on an executive functioning rating scale compares to parent report and that of youth with attention deficit hyperactivity disorder or neurotypical development. (February 2022) - Kenworthy, Lauren; Verbalis, Alyssa; Bascom, Julia; daVanport, Sharon; Strang, John F; Pugliese, Cara; Freeman, Andrew; Jeppsen, Charlotte; Armour, Anna C; Jost, Geneva; Hardy, Kristina; Wallace, Gregory L
Executive functions are related to key outcomes. Studies of autistic youth self-report of other nonsocial traits indicate that their insights into their own functioning and internal experiences provide important information that is not captured by their parents' report, but youth self-report of executive function has not been researched in autism. We investigate self- and parent-report on the Behavior Rating Inventory of Executive Function-2 in 197 autistic youth without intellectual disability, including the magnitude and profile of problems reported across subdomains of executive function. We also compare autistic self-report to that of 114 youth with attention deficit hyperactivity disorder and 197 neurotypical youth. We find that autistic youth report significant executive function challenges in comparison to neurotypical youth and a distinctive profile of challenges in comparison to attention deficit hyperactivity disorder youth. Parents and their autistic children diverge regarding the severity of the youth's executive function difficulties, but both emphasize flexibility problems within their profile of executive function challenges. Intraclass correlation coefficients between parent and youth ratings were moderate to poor in the autistic group, indicating that autistic youth report adds important information beyond that captured by their parents' report. These data elevate the importance of asking autistic youth directly about their own executive function. Lay abstract: Executive functions are often impaired in autistic people and relate to important outcomes such as mental health, success in school and work, and quality of life. Evaluating executive functions helps autistic people, clinicians, and families identify targets for external supports and skill building. Youth self-report of executive function has not been studied, yet we know that self-report from autistic youth is key to understanding other cognitive/behavioral phenomena in autism such as anxiety, obsessions/compulsions, sensory sensitivities, and repetitive behaviors. We investigated self- and parent-report of executive function problems in 197 autistic youth without intellectual disability (ages 11–18 years), including the magnitude and profiles of executive function problems autistic youth report across subdomains of executive function. We compared autistic self-report with that of 114 youth with attention deficit hyperactivity disorder without intellectual disability and 197 neurotypical youth. We found that autistic youth report significant executive function problems compared to neurotypical youth and a distinctive profile of challenges in comparison to attention deficit hyperactivity disorder youth. Parents and their autistic children diverged regarding the magnitude of the youth's executive function difficulties, but both identify inflexibility as the most impaired executive function subdomain. Autistic youth and their parents were somewhat more concordant in their report of executive function problems than youth with attention deficit hyperactivity disorder and their parents, but only showed moderate concordance at best. These findings elevate the importance of asking autistic youth directly about their executive functioning when engaging them in assessment and intervention, or researching executive functions in autism.